2012
DOI: 10.1371/journal.pone.0045237
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Properties of Differentiating Blood Cells Are Fate- and Function-Dependent

Abstract: Although cellular mechanical properties are known to alter during stem cell differentiation, understanding of the functional relevance of such alterations is incomplete. Here, we show that during the course of differentiation of human myeloid precursor cells into three different lineages, the cells alter their viscoelastic properties, measured using an optical stretcher, to suit their ultimate fate and function. Myeloid cells circulating in blood have to be advected through constrictions in blood vessels, enge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
191
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(201 citation statements)
references
References 38 publications
(52 reference statements)
9
191
1
Order By: Relevance
“…HL-60 cells also exhibit similar mechanical properties; recent measurements of cell compliance using an optical stretcher confirmed that in vitro differentiation of HL-60 cells into neutrophil-type cells recapitulates the 3-6-fold increase in cell deformability observed in primary neutrophils and their CD34ϩ precursor cells (31). A direct comparison of the absolute passage times through micron-sized constriction between primary neutrophils and HL-60-derived neutrophil-type cells is complicated by the fact that HL-60 cells are typically larger than primary neutrophils (ϳ12-m versus 7-8-m median diameter, respectively) and exhibit substantially larger transit times through microfluidic constriction channels (29).…”
Section: Discussionmentioning
confidence: 79%
“…HL-60 cells also exhibit similar mechanical properties; recent measurements of cell compliance using an optical stretcher confirmed that in vitro differentiation of HL-60 cells into neutrophil-type cells recapitulates the 3-6-fold increase in cell deformability observed in primary neutrophils and their CD34ϩ precursor cells (31). A direct comparison of the absolute passage times through micron-sized constriction between primary neutrophils and HL-60-derived neutrophil-type cells is complicated by the fact that HL-60 cells are typically larger than primary neutrophils (ϳ12-m versus 7-8-m median diameter, respectively) and exhibit substantially larger transit times through microfluidic constriction channels (29).…”
Section: Discussionmentioning
confidence: 79%
“…Alterations in cell properties are of fundamental importance for a wide range of processes, and changes in cell mechanics are associated with conditions such as osteoarthritis [8], asthma [9], cancer [10], inflammation [11] and malaria [12]. The mechanical properties of living cells have been quantified using various testing methods, such as micropipette aspiration [8,13], magnetic twisting cytometry [14], optical tweezers [15][16][17] and nanoindentation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…17 Most of these methods require fully integrated sensors or additional tedious calibration procedure using a standard reference. On the other hand, viscoelasticity measurement of fluids has been conducted using ferromagnetic micro-beads, 18 optically-induced force, 19 squeeze flows, 20,21 flexible polymer-based deflection, 22,23 micro-PIV, 24 and extensional flow. 25,26 However, most of these previous studies focused on measuring the relaxation time rather than elasticity itself because these methods may not have the ability to concurrently measure fluid viscosity.…”
Section: Introductionmentioning
confidence: 99%